Religious Moderation, Pela Gandong and Jihad Reconstruction: Conflict Prevention in Maluku from the Perspective of Maqāṣid Al-Sharī'ah - Arsyad, Azman; Daud, Mahmuddin; Idris, Aisyah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This article analyzes religious moderation, pela gandong, and the reconfiguration of jihad to prevent war in Maluku. Conflict avoidance has been viable through a sophisticated understanding of religion, utilizing cultural mechanisms like pela gandong. The research utilized an empirical methodology analyzed via the framework of maqāṣid al-sharī'ah theory. Data were obtained through extensive interviews and literature reviews to guarantee accuracy. The interviewed participants were individuals impacted by the war, community leaders, religious figures, scholars, and female leaders. The study concluded that the violence in Maluku was initially triggered by economic imbalances impacting social, political, and religious aspects. Moreover, the Maluku community throughout the conflict was regarded as a battleground, influenced by external group dynamics. Conflict prevention in Ambon can be accomplished by constructively reinterpreting jihad, fostering religious moderation, and revitalizing culture through pela gandong. Pela gandong is a tradition that strengthens social ties, highlighting a commitment to mutual respect, collaboration, and the maintenance of harmonious relations between two community groups, so promoting reconciliation and peace-building efforts. In the context of maqāṣid al-sharī'ah, which asserts that the aim of the Islamic law is to provide substantial advantages to humanity, the integration of culture and the precise interpretation of jihad is essential. Consequently, within the realm of Islamic jurisprudence, a contextual interpretation of jihad will provide a more beneficial comprehension than a textual examination. The basic purpose of Islamic law is to establish peace and harmony while preventing conflict within society.